Correlation between Serum Amyloid a and White Blood Cell Count in Patients with Bacterial Skin Infections - Radhi, Lamyaa. Y. (American Journal of Biology and Natural Sciences, 2025)
Background: Acute inflammatory reactions to bacterial skin infections result in the high concentration of serum biomarkers like serum amyloid A (SAA) and the high concentration of white blood cells (WBC) and hence the relationship between them is useful in evaluating the severity of the infection. Aims of the study: The proposed research objective is to determine the relationship between the serum amyloid A (SAA) and the count of the white blood cells (WBC) in patients with a bacterial skin infection to understand their diagnostic and prognostic value. Methodology: The study was a prospective case-control study (10 April- 10 August 2025) that involved 80 bacterial skin-infected patients and 50 controls who are healthy. Diagnosis was clinical and culture supported. Adults (adults over 18 years) were enrolled lately infected; the ones with chronic disease or recent antibiotics were excluded. CBC, SAA (ELISA) and CRP (immunoturbidimetry) were also sampled using blood. All the tests were done within two hours under normal quality control. Result: The age, gender, BMI and smoking of the patients (n=80) and the controls (n=50) showed no significant differences so that the groups could be compared. There was significant increase in inflammatory markers in patients: SAA (148.6 mg/L vs 5.2), WBC (12.8 vs 6.5 ×10 3/ uL), neutrophils (9.4 vs 3.8), and CRP (38.7 vs 2.1) (P < 0.001). Most common were Cellulitis (40) and abscess (31.3). SAA was closely related to WBC, neutrophils, CRP, and temperature. The level of markers increased dramatically as the severity of infections increased. Conclusions: The research comes to a conclusion that high levels of SAA, WBC, neutrophils and CRP are powerful indicators of the severity of bacterial skin infections. These biomarkers are indicators of the acute inflammatory response, which is caused by cytokine release and the recruitment of neutrophils, and thus they can be useful in the diagnosis and evaluation of severity.